2016
DOI: 10.3389/fmicb.2016.01474
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Freshwater and Terrestrial Sources Are Differentially Reflected in the Bacterial Community Structure along a Small Arctic River and Its Estuary

Abstract: Glacier melting and altered precipitation patterns influence Arctic freshwater and coastal ecosystems. Arctic rivers are central to Arctic water ecosystems by linking glacier meltwaters and precipitation with the ocean through transport of particulate matter and microorganisms. However, the impact of different water sources on the microbial communities in Arctic rivers and estuaries remains unknown. In this study we used 16S rRNA gene amplicon sequencing to assess a small river and its estuary on the Disko Isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…The bacterial communities in the rivers were highly specific to each of them (Figure 8), which we suggest is due to their difference in origin and catchment area; close connection (0.5 km) to the Greenland Ice Sheet (R1), longer distance (2 km) from smaller local glacier (R2), and the lowland vegetation rich river with lake connection (R3). This is in agreement with a recent study from West Greenland that similarly show distinct communities in rivers and a proglacial lake over a 2 km distance (Hauptmann et al, 2016), and find less terrestrial species in river samples with a more direct connection to glaciers.…”
Section: Bacterial Community Compositionsupporting
confidence: 93%
“…The bacterial communities in the rivers were highly specific to each of them (Figure 8), which we suggest is due to their difference in origin and catchment area; close connection (0.5 km) to the Greenland Ice Sheet (R1), longer distance (2 km) from smaller local glacier (R2), and the lowland vegetation rich river with lake connection (R3). This is in agreement with a recent study from West Greenland that similarly show distinct communities in rivers and a proglacial lake over a 2 km distance (Hauptmann et al, 2016), and find less terrestrial species in river samples with a more direct connection to glaciers.…”
Section: Bacterial Community Compositionsupporting
confidence: 93%
“…The FDOM signals from the three rivers were directly related to their catchment, with the glacial rivers R1 and R2 supplying similar and low signal, while the tundra and lakes in the R3 catchment supply an elevated and more variable signal. Similar variations in FDOM intensity of large Arctic rivers have been explained by the difference in the vegetation characteristics of the catchment (Walker et al ), further the presence of proglacial lakes results in higher DOC concentrations (340–406 μ M C) (Bhatia et al ; Hauptmann et al ). The low‐carbon content in glacial meltwater in Young Sound is consistent previous observations from the western part of Greenland Ice Sheet with 7–32 μ M C, 15–51 μ M C, and 21–100 μ M C found in subglacial, supraglacial discharge, and a glacial stream with connection to a proglacial lake, respectively (Bhatia et al ; Lawson et al ; Hauptmann et al ).…”
Section: Discussionmentioning
confidence: 59%
“…It has been previously reported that the microbial community in both surface and subsurface soils from Tibet are influenced by total carbon and the carbon to nitrogen ratio . The total bacterial community structure in a small Arctic river was significantly correlated with turbidity, but the estuary bacterial community was not significantly correlated with any environmental factor . Thus bacterial communities in different ecosystems are influenced by different environmental variables.…”
Section: Discussionmentioning
confidence: 88%
“…A previous study suggested that sediments have a higher bacterial diversity than any other type of environment at a global scale . The diversity and community composition of bacteria in river sediments are distinct from those in estuary sediments . Abundance and activity of bacteria in the marine and brackish water zones are distinct due to different freshwater regimes .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation